A Cross-Sectional Study of Dairy Cattle Metagenomes Reveals Increased Antimicrobial Resistance in Animals Farmed in a Heavy Metal Contaminated Environment - Gaeta, Natalia Carrillo; Bean, Emily; Miles, Asha Marie; Carvalho, Daniel Ubriaco Oliveira Gonçalves de; Alemán, Mario Augusto Reyes; Carvalho, Jeferson Silva; Gregory, Lilian; Ganda, Erika (Frontiers in Microbiology, 2020)
The use of heavy metals in economic and social development can create an accumulation of toxic waste in the environment. High concentrations of heavy metals can damage human and animal health, lead to the development of antibiotic resistance, and possibly change microbiomes. It is important to investigate the influence of heavy metals in food systems to determine potential effects on human health. We investigated the consequences of long-term exposure to contaminated drinking water on the metagenomes of dairy cattle, following a mining dam rupture in which 43 million cubic meters of iron ore waste flowed into the Doce river basin surrounding Mariana City, Brazil, in 2015. We measured bacterial antimicrobial resistance genes in the feces, rumen, and nasopharynx of 16 dairy cattle four years following the environmental disaster (A) and compared them to analogous samples from 16 dairy cattle in an unaffected farm, 356 km away (B). The metagenomes of farm A and farm B differed in many aspects. The distribution of genes conferring antimicrobial resistance was highly heterogeneous, and most genes were present in only a few samples. The abundance and prevalence of antimicrobial resistance (AMR) genes were higher in the affected farm (A) than in the unaffected farm (B). Samples from farm A had a higher prevalence of genes conferring resistance to multiple drugs, metals, biocides, and multi-compound resistance. Fecal samples had a higher relative abundance of AMR genes, followed by rumen samples, and the nasopharynx had the lowest amount of AMR genes detected. Metagenome functional annotation suggested that selective pressures of heavy metal exposure potentially skewed pathway diversity towards fewer, more specialized functions. This is the first study that evaluates the consequences of a Brazilian environmental accident with mining ore dam failure in the microbiome of dairy cows. Our findings suggest that the long-term persistence of heavy metals in the environment may result in differences in the microbiota, enrichment of antimicrobial- resistant bacteria, and that AMR genes are most readily detected in fecal samples. Since heavy metal contamination has an effect on the animal microbiome, environmental management is warranted to protect the food system from hazardous consequences.